2021
DOI: 10.1053/j.jfas.2020.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Microfracture Technique Versus Microfracture in Talar Cartilage Restoration: A Systematic Review and Meta-Analysis

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…In smaller lesions, the additional scaffolds did not change the clinical outcome. However, patients benefit from biological support (65,66).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In smaller lesions, the additional scaffolds did not change the clinical outcome. However, patients benefit from biological support (65,66).…”
Section: Discussionmentioning
confidence: 99%
“…One study by Migliorini et al(64) with a 5-year follow-up compared M-BMS (matrix-associated BMS) using Chondro-Gide® against BMS, and they reported significantly better results with the additional scaffold in lesions sized between 2 and 3 cm². In a systematic review and meta-analysis, Wen et al(65) included studies comparing microfracture alone against microfracture with additional biological augmentation such as scaffolds, hyaluronic acid, platelet-rich plasma (PRP), Statement: Good results are reported for BMS in small lesions, including a high rate of return to sports. Unstable cartilage and small bony fragments should be removed.…”
mentioning
confidence: 99%
“…Studies with the goat model for cartilage repair have demonstrated success in therapy with fetal progenitor cells and Wharton’s jelly derived mesenchymal stem cells (hWJMSCs) [ 69 ] and BMSCs alone or associated with scaffolds or GDFs [ 69 , 71 , 72 ]. Zhang et al (2018) studied the potential of the hWJMSCs in a caprine model with a full-thickness femoral condyle articular cartilage defect, compared with the MF technique.…”
Section: Application Of Mscs In the Goat Modelmentioning
confidence: 99%